2017
DOI: 10.2147/jaa.s124902
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-like airway inflammation and responses in a rat model of atopic dermatitis induced by neonatal capsaicin treatment

Abstract: Abstract:Recent studies have shown that approximately 70% of patients with severe atopic dermatitis (AD) develop asthma. Development of AD in infancy and subsequent other atopic diseases such as asthma in childhood is referred to as atopic march. However, a causal link between the diseases of atopic march has remained largely unaddressed, possibly due to lack of a proper animal model. Recently, we developed an AD rat model showing chronically relapsing dermatitis and scratching behaviors induced by neonatal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In rodent models, Th2 cytokine profile (interleukin 4 [IL-4], IL-5 and IL-13) has been well documented. 15 , 20 , 32 In a feline model, IL-4 has been demonstrated in airway allergic inflammation, 33 while in a sheep asthma model recently published, it has been demonstrated that both IL-4 and IL-13 increase in BAL after allergen challenge. 34 In equines, former studies were controversial in terms of inflammation pattern, ranging from Th1, Th2 and Th17 cytokines profile, 35 , 36 but recent studies have shown that inflammation seems to be mainly mediated by Th17 cytokines, like CXCL13 and IL-17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent models, Th2 cytokine profile (interleukin 4 [IL-4], IL-5 and IL-13) has been well documented. 15 , 20 , 32 In a feline model, IL-4 has been demonstrated in airway allergic inflammation, 33 while in a sheep asthma model recently published, it has been demonstrated that both IL-4 and IL-13 increase in BAL after allergen challenge. 34 In equines, former studies were controversial in terms of inflammation pattern, ranging from Th1, Th2 and Th17 cytokines profile, 35 , 36 but recent studies have shown that inflammation seems to be mainly mediated by Th17 cytokines, like CXCL13 and IL-17.…”
Section: Introductionmentioning
confidence: 99%
“…Once IgE is produced, it will bind to the high-affinity receptor FcεR1 on the surface of mast cells and basophils. 32 , 33 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study has demonstrated that treating neonatal Sprague Dawley rats with capsaicin can result in an asthma-like phenotype, as evidenced by changes in the IgE levels; an increased number of eosinophils in the BAL fluid; and the increased mRNA expression of Th2 cytokines (such as IL-4, IL-5, and IL-13) in the lung tissue, as well as decreased airway resistance and compliance [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…IgE levels in the plasma and in the supernatant produced from the BAL fluid were measured using a rat IgE ELISA kit (Cusabio, Houston, TX, USA) [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Asthma is a well-known chronic disease of the lungs that affects the airways (Martinez 2007 ). Primary symptoms of asthma include bronchospasm, airflow obstruction, chest tightness, coughing, wheezing, and shortness of breath (Han et al 2017 ). Asthma cannot be cured permanently; only the symptoms can be ameliorated by medications (Han et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%